Digital technologies: promoting sustainable development for the youth field - Zarpelon, Mirian Cátia; Kolcenti, Cassiane; Balestrin, Deisi; Tortelli, Luana; Blazszack, Vinicíus; Guedes, Anibal Lopes (Revista Eletrônica em Gestão, Educação e Tecnologia Ambiental, 2015)
The sustainable development is nowadays one of the main challenges being faced today. Included in this universe agriculture, through the consolidation of productive activities in order to develop sustainably managing rural property as well as its environmental and social conditions, without degrading the natural capital and maintaining the well being of society. Within this process, new technologies provide the development of simple creative solutions to improve life in the countryside, through the use of automated mechanisms and recycled materials. Thus, if the want to discuss the concept of sustainability, environmental and new technologies in order to support the field. The methodology proposed to study the arduino robotic kit in the field, being an open source development tool and electronic prototyping, easy to use and a flexible hardware and software. Finally, we are part of nature and that it is not composed only by human beings. All beings are interdependent and form a community of life. The network, this connectivity is derived, is responsible for the balance of life and the planet.